Ocular Features and Visual Outcome in Children with Moyamoya Disease and Moyamoya Syndrome: A Case Series - John, Deepa (J Clin Diagn Res, 2016)
Moya Moya Disease (MMD) is characterised by idiopathic vasculopathy affecting the terminal internal carotid arteries resulting in the formation of extensive collaterals at the base of the brain, leptomeninges and parenchymal regions with resultant infarcts and bleeds. Four children presented with clinico-radiological features suggestive of Moyamoya disease/syndrome. This includes global developmental delay, recurrent seizures, transient ischaemic attacks and impaired vision. The first patient had vision of 6/15 in both eyes with bilateral optic disc pallor. Second case also had bilateral optic disc pallor with arteriolar attenuation, but had vision of perception of light only in both eyes. The third child had vision of 6/60 with alternate divergent squint and clinical features suggestive of Neurofibromatosis 1 (NF 1). Fourth patient presented with poor fixation in both eyes with bilateral total cataract. He underwent bilateral cataract surgery with intraocular lens implantation and vision improved to 2/60 with good fixation. We also describe their medical and neurosurgical interventions in this report.